Analisis Perbandingan Tes Kepribadian Objektif dan Proyektif dalam Mengungkap Kepribadian Individu: Kelebihan, Kekurangan, dan Analisis Waktu Penggunaan Tes yang Ideal - Farida Muji Rahayu (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Psychological tests are important tools used to uncover various aspects of an individual's personality according to the needs of psychological assessment. One widely used form of psychological testing is the personality test, which is generally divided into two main types: objective and projective. This study aims to analyze the effectiveness of both types of tests in uncovering aspects of an individual's personality by comparing their respective advantages and disadvantages. The research method used was a qualitative method with a literature review approach, namely through a review of various scientific articles, research journals, and relevant literature sources discussing the use of objective and projective personality tests. The results show that each type of test has distinct characteristics and functions. Objective tests are considered more reliable, efficient, and easy to interpret, while projective tests provide a more in-depth picture of an individual's personality dynamics but require more subjective interpretation. Furthermore, this study also analyzes the ideal conditions and timing for use of both types of tests and presents case studies of the application of each test in the context of psychological assessment.